Characteristic analysis of densified wood residues [compact disc] - 343039 Wong, Tiong Hui (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006